Perbandingan Kompresi NTFS Terhadap Kompresi Lain dari Tingkat Kompresi dan Kecepatan Baca dan Tulis - Azzahra, Fadel; Sihombing, Rudolf Paris Parlindungan; Simanjuntak, Mirza Uliartha; Kardian, Aqwam Rosadi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
This study aims to compare the read and write speed levels between NTFS compression and compression in software, both with the Lempel-Ziv algorithm and other algorithms. Results were retrieved by comparing the compression and decompression rates using the NTFS file system and the 7-Zip application which was performed using files with different file types and sizes. It is concluded that NTFS compression with process automation capability is quite good in terms of read and write speed, although in terms of compression level it is still not as good as compression in software. This research does not only compare one file compression algorithm to another, but also how the algorithm is implemented in different ways/media, in this case on the NTFS file system and on third-party software (7-Zip).